An Investigative Study on Cache-Oblivious Data Structures - Dwarampudi Aiswarya; Manas Kumar Yogi (International Journal of Data Structure Studies, 2024)
Cache-oblivious data structures and data management systems have emerged as critical components in modern computing environments, aiming to optimize memory access patterns across different levels of the memory hierarchy without explicit knowledge of cache sizes or configurations. This study presents an overview of cache-oblivious techniques, including adaptive data structures, compression, parallel processing, and security considerations. The workexplores future directions in cache-oblivious systems, such as non-volatile memory support, graph processing, edge computing, energy efficiency, and machine learning applications. Furthermore, empirical evaluation and benchmarking methodologies are discussed to assess the practical performance of cache-oblivious solutions on diverse hardware platforms and workloads. By addressing these challenges and opportunities, cache-oblivious data structures and management systems have the potential to revolutionize memory management, storage optimization, and computational efficiency in a wide range of computing domains.
Keywords: Cache-Oblivious Algorithms; Security and Privacy; data structures